Toxicity of Hoechst 33342: implication in side population analysis - Zheng, J; Qi, S; Zhu, H; Xiao, X (Cellular and Molecular Biology, 2016)
In the current study, we discovered that Hoechst 33342 (H342) could produce significant toxicity to the human neuroblastoma SK-N-SH cells at concentrations typically used to identify side population (SP) cells. At 3.75 and 5 µg/ml, H342 induced cell death and apoptosis. Flow cytometry analysis revealed cell cycle arrest at S-phase. Our findings caution against using H342 for SP analysis without considering differential susceptibility of different cells to H342. Specifically, concentration of H342 needs to be adjusted carefully to minimize toxicity for each cell line.